Scoring heart rate increases as a surrogate arousal marker on portable monitor studies for obstructive sleep apnea: Impact on diagnostic accuracy and clinical decision‐making. (19th April 2022) - Lachapelle, Philippe; Khadadah, Sulaiman; Taseen, Ryeyan; Pamidi, Sushmita; Kimoff, R. John
Summary: Cortical arousal‐related hypopneas are not scored on type 3 home devices, which therefore limits their diagnostic accuracy for obstructive sleep apnea. The objective of this study was to evaluate whether scoring heart rate accelerations as surrogate markers of arousal improves type 3 portable monitor diagnostic agreement compared with polysomnography and improves therapeutic decision‐making. We prospectively recruited patients evaluated for obstructive sleep apnea to undergo in‐laboratory simultaneous full polysomnography + type 3 portable monitoring. Hypopnea events were scored on portable monitor studies with and without autonomic scoring, which was defined as an associated increase in pulse oximetry‐derived heart rate ≥6 beats per min (autonomic hypopnea). Portable monitor diagnostic agreement compared with polysomnography with and without autonomic hypopnea scoring was assessed. We also evaluated whether reporting autonomic hypopnea scoring improves portable monitor clinical treatment decision agreement after four physicians reviewed clinical data and sleep study results (polysomnography, portable monitor with autonomic hypopnea, portable monitor without autonomic hypopnea). Eighty‐two participants completed simultaneous polysomnography and in‐laboratory portable monitor studies. Scoring autonomic hypopnea resulted in a decreased mean difference between in‐laboratory portable monitor respiratory event index and polysomnography apnea–hypopnea index in Bland–Altman analysis (mean difference 14.6 per hr without versus 6.1 per hr with autonomic hypopnea scoring [ p  ˂ 0.01]), and increased intraclass correlation from 0.769 to 0.844. Inclusion of autonomic hypopnea scoring resulted in better accuracy between portable monitor and polysomnography expert's treatment decisions, and ultimately resulted in 24% fewer additional polysomnographies requested. The addition of pulse oximetry heart rate increases for autonomic hypopnea scoring during portable monitor resulted in better diagnostic agreement, improved clinical decision‐making and reduced additional polysomnography testing.